High Serological Evidence of Human Papillomavirus Type 16 Infection in Women of Child-Bearing Age in Central Nigeria. (March 2022) - Adoga, M.; Abubakar, K.; Oti, V.; Diya, A.; Reuben, R.
Abstract : Purpose: Globally, Human Papillomavirus Types 16 (HPV-16) and 18 (HPV-18) are responsible for about 70.0 % of cervical cancers and pre-cancerous cervical lesions. However, although cervical cancer is the second most common cancer and the leading cause of cancer death in women in sub-Saharan Africa, the presence of HPV antibodies which are considered as markers of cumulative exposure are not routinely screened among women in Nigeria. This is the first study to determine the seroprevalence of HPV-16 specific IgG antibodies and associated risk factors among women of child-bearing age in central Nigeria. Methods & Materials: In a cross-sectional study, the seroprevalence of HPV-16 IgG antibodies was assessed using HPV-16 specific IgG enzyme-linked immunosorbent assay of sera samples from 400 consenting women. Also, information regarding socio-demographics and HPV risk determinants were simultaneously obtained. Results: Overall, 128 (32.0%) of the study population were seropositive for HPV-16 IgG antibodies. Women within the age groups of 15-19, 20-24, 25-29, 30-34, 35-39, 40-44 and 45-49 years had the prevalence of 50.0, 55.5, 12.9, 50.0, 32.1, 18.2 and 19.4% respectively (P < 0.05; 95% CI 5.06-31.51). Seropositivity was positively correlated with the number of sexual partners and history of genital warts. Furthermore, significant predictors to HPV-16 as recorded in this study were age, occupation, number of sex partners and education level (P < 0.05). Conclusion: The findings from this study provide important insights into the burden of HPV infection in central Nigeria with implications for national and regional intervention initiatives including high-level advocacy, population-wide screening and vaccination programmes.